2018
DOI: 10.1007/s11655-018-2836-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune Homeostasis: Effects of Chinese Herbal Formulae and Herb-Derived Compounds on Allergic Asthma in Different Experimental Models

Abstract: Allergic asthma is thought to arise from an imbalance of immune regulation, which is characterized by the production of large quantities of IgE antibodies by B cells and a decrease of the interferon-γ/interleukin-4 (Th1/Th2) ratio. Certain immunomodulatory components and Chinese herbal formulae have been used in traditional herbal medicine for thousands of years. However, there are few studies performing evidence-based Chinese medicine (CM) research on the mechanisms and effificacy of these drugs in allergic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Asthma is a common disease characterized by bronchial hyperesponsiveness, lung infiltration of inflammatory cells, and airway remodeling . Around 300 million patients suffer from asthma on an annual basis, and the incidence has been increasing in the past 2 decades .…”
mentioning
confidence: 99%
“…Asthma is a common disease characterized by bronchial hyperesponsiveness, lung infiltration of inflammatory cells, and airway remodeling . Around 300 million patients suffer from asthma on an annual basis, and the incidence has been increasing in the past 2 decades .…”
mentioning
confidence: 99%
“…Regulatory T cells (Tregs), as well as transforming growth factor-b (TGF-b) and IL-10, are known to have important inhibitory functions in CD4 + T-cell proliferation (34)(35)(36). In addition, a variety of plants have been implicated to have the ability to regulate immune response (37,38). Indeed, our current study revealed that DH exhibits potent anti-proliferative effects on autoreactive CD4 + T cells and ameliorates the development of experimental autoimmune uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…The chronicity of asthma imposes a heavy economic burden on the patients. Recently, a traditional Chinese medicine herb was reported to have a strong curative effect on asthma in a clinical study and in asthmatic animal models (Gandhi et al, ; Liu, Wang, He, & Ma, ). Some studies also reported the diterpene substance (such as phytol) with the antiradical, antimicrobial and cytotoxic activities in vitro (Pejin, Ciric, Glamoclija, Nikolic, & Sokovic, ; Pejin, Kojic, & Bogdanovic, ; Pejin, Savic, et al, ).…”
Section: Discussionmentioning
confidence: 99%